Amphipod protein, glycogen, and glucose content under simulated invasion stress in wetlands - Tanner, Richelle L; Haworth, Lorna E; Nancollas, Sarah; Landa, Susie N; Todgham, Anne E (PANGAEA, 2024)
Amphipods (Gammarus sp.) were observed and collected from the Tule Red Tidal Restoration Site in Suisun Marsh (38.117843, -121.983199) in January-December 2021. All observations and collections were conducted in <20 cm of brackish water in secondary tidal channels on the restoration site within 0.25 miles of the provided GPS coordinates. All amphipods were collected under California Scientific Collecting Permit No. S-201970002-20281-001. Monthly field observations and captures were done at 5 m intervals over eight semi-permanent 20 m transects established in paired Phragmites and native plant canopies in the same area of the marsh, where 0 m indicated the edge of a tidal channel. We measured pelagic invertebrate biodiversity by capturing discrete water pools (~60 g water) using a turkey baster. The water samples were sieved using a 0.125 mm filter and rinsed with deionized water before preservation in a rose bengal-dyed 70% ethanol solution. We also measured benthic invertebrate biodiversity with a sediment mud core (5 cm diameter and 10 cm depth). The benthic samples were sieved and washed using a 0.5 mm filter and rinsed with deionized water before preservation in a rose bengal-dyed 70% ethanol solution. Preserved samples were sorted, counted, and photographed under a dissecting microscope. Counts per sample were normalized to the weight of the original sample. Eight HOBO Pendant Temperature/Light 64K Data Loggers (Onset Computers) were installed among native and Phragmites canopies (n = 4 each) in the Tule Red Tidal Restoration Project within Suisun Marsh (38.118588, -121.980767). Four of these loggers were placed at the edge of a secondary tidal channel in the vegetation stand and four were placed 20 m perpendicular to the tidal channel onto the marsh plain. The loggers recorded temperature (°C) and light intensity (lumens/ft², or lux) continuously every 15 minutes from October 2020 through December 2021. The data used to create the laboratory conditions were isolated from the first 10 days of May 2021. The most extreme representations of each habitat (native and Phragmites) were used as the environmental conditions for each laboratory treatment: 12.7-35.7 °C and 11,229 lumens for the native habitat and 13.6-24.3 °C and 3,341 lumens for the Phragmites habitat, both on a semidiurnal tidal cycle. Amphipods were collected from the Tule Red Tidal Restoration site in Suisun Marsh, CA (38.117843, -121.983199) in July 2021. Using fine mesh nylon aquarium nets, adult amphipods (>0.5 cm in length) collected from a small channel and held in water-filled coolers. 24 individuals were collected for two habitat types (under native vegetation, under Phragmites vegetation) and immediately frozen on dry ice in the field to be used as controls in the following biochemical assays (below as "Week 0"). Collection and transport to the UC Davis Center for Aquatic Biology and Aquaculture were completed in <5 hours. Amphipods were housed in closed-system aquaria manually fed by marsh water collected at the mouth of the same tidal marsh (38.133841, -121.995977). In the lab, the marsh water was held in a darkened 1500 l sump tank and continuously aerated to reduce excessive algal growth (salinity = 6.3 psu). We randomly placed 120 amphipods into each of 16 tanks (n = 1,920 total). They were acclimated in common garden conditions at 15 °C for two days before experimental conditions were imposed for a 6-week laboratory acclimation period. In a fully crossed design, we exposed four replicate tanks each to the following four combinations of light and temperature exposure: native temperature/native light, native temperature/Phragmites light, Phragmites temperature/Phragmites light, and Phragmites temperature/native light. Amphipods were fed shrimp food pellets (Sera Shrimps Natural Nature Food) ad libitum three times per week. 50% of the water volume in each tank was replaced weekly using 0.125 mm filtered water from the 1500 l sump tank. Every two weeks during the 6-week acclimation period, 16 adults were randomly selected from each tank and sorted into two groups for protein and glycogen analyses (n = 8 for each analysis). Individuals were sacrificed in dry ice and stored at -80 °C. Prior to the homogenization of tissues, the presence/absence of eggs was recorded for each amphipod selected. The total number of juvenile amphipods in each tank was counted at the time of random selection. Whole frozen amphipods were prepared for protein quantification using a colorimetric assay (Thermo Scientific Pierce BCA Protein Assay Kit). Samples were homogenized with a Pro200 Bio-Gen Series homogenizer for 10 seconds on ice with the homogenization buffer (100 mmol l⁻¹ Tris-HCl, pH 7.5; 0.1% SDS (w/v), 0.5 mol l⁻¹ EDTA) containing a combination of protease inhibitors: 0.7 μg ml⁻¹ pepstatin A, 0.5 μg ml⁻¹ leupeptin, 1 μg ml⁻¹ aprotinin and 20 μg ml⁻¹ phenylmethylsulfonyl fluoride at a dilution ratio of 1:20. In several instances, protein concentration at a 1:20 dilution was too high for the range of measurement: seven individuals were further diluted to 1:30 and two individuals were further diluted to 1:35. Homogenates were centrifuged at 13,000 g for 10 minutes. 50 μl of the resulting supernatant was transferred into a new 0.5 ml tube to use for total protein quantification. 10 μl of each sample was added to triplicate wells in 96 well plates. 200 μl of the BCA reagent was added to the wells and then placed on the shaker for 30 seconds. Plates were heated at 37 °C for 30 minutes and placed on the spectrometer at 562 nm. Protein values were standardized with 2 mg ml⁻¹ BSA standard. Frozen amphipods were ground into fine powder using a liquid nitrogen cooled mortar and pestle. Glucose and glycogen metabolites were extracted separately to be analyzed using a colorimetric assay. Glycogen was extracted by adding 1 ml of ice-cold 8% HClO₄ to approximately 20 mg of powdered amphipod tissue and then homogenized on ice for approximately 10 seconds with a Pro200 Bio-Gen Series homogenizer (PROScientific, Oxford, CT, USA). A 200 μl sample of the homogenate was frozen at -80 °C for later glycogen analysis. The remaining homogenate slurry was centrifuged at 10,000 g for 10 minutes at 4 °C and the supernatant was extracted and neutralized with 3 mol l⁻¹ K₂CO₃. The solution was centrifuged again at 10,000 g for 10 minutes at 4 °C and frozen at -80 °C for the glucose assay. Glycogen samples were enzymatically digested using previous methods (Hassid & Abraham, 1957) and analyzed for glucose following methodology (Bergmeyer, 1983) modified for microplate spectrophotometer (Synergy HT, Biotek, Winooski, VT, USA). Glycogen content was then corrected for starting glucose.
Keywords: Amphipoda; Field observation; invasion ecology; Laboratory experiment; physiology; wetland